Analysis of Three Level Diode Clamped Multilevel Fed Induction Motor Drive (International Journal of Engineering and Computer Science, 2017)
A multilevel inverter is a power electronic device that is widely applied in industries for high voltage and high power applications, with the added remuneration of low switching stress and lower total harmonic distortion (THD), hence dropping the size and volume of the passive filters. Multilevel inverter machinery has emerged recently as a very important alternative in the area of high power medium-voltage control and also for improving the total harmonic distortion by reducing the harmonics. Generally, the poor quality of voltage and current of a conventional inverter fed induction machine is obtained due to the presence of harmonics and hence there is a significant level of energy losses. The objective of this paper is to obtain a 3-level output, which is acquire by a three phase three level diode clamped multilevel inverter (MLI) fed induction motor drive. This paper presents the simulation result and implementation of three phase three level multilevel inverter (MLI) fed induction motor Drive.